Differential Acceptance of Advance Directives Between Millennials and Baby Boomer Generations: A Cross-Sectional Survey Study Among College Students and Their Relatives. Issue 3 (July 2022) - Liang, Yia-Wun; Lin, Yu-Hsiu; Chen, Su-Ting
Objectives: This study aims to explore the differentials of knowledge and attitude of advance directives (ADs) between millennials and baby boomer generations, and the effects of the intention to sign the advance directives.Methods: This is a cross-sectional study using a self-administered questionnaire to collect data from 325 students in a health-related college of a University of Science and Technology in Taiwan, and their parents, as total of 226, who are baby boomers. The statistical methods include descriptive statistics and inferential statistics.Results: Only 10 people from the 2 generations signed an AD. The multivariate logistic regression showed that baby boomer generation, AD knowledge, and AD attitude were significant positive associate of willingness to sign AD in the future.Conclusions: The government may enhance promotion of ADs among millennials and improve the connection between millennials' knowledge of and attitude toward ADs, and their AD signing behavior.